Language Separation in Bidialectal Speakers: Evidence From Eye Tracking - Lundquist, Björn; Vangsnes, Øystein A. (Frontiers in Psychology, 2018)
The aim of this study was to find out how people process the dialectal variation encountered in the daily linguistic input. We conducted an eye tracking study (Visual Word Paradigm) that targeted the predictive processing of grammatical gender markers. Three different groups of Norwegian speakers took part in the experiment: one group of students from the capital Oslo, and two groups of dialect speakers from the Western Norwegian town Sogndal. One Sogndal group was defined as ``stable dialect speakers'', and one as ``unstable dialect speakers'', based on a background questionnaire. The students participated in two eye tracking experiments each, one conducted in the their own dialect, and one in the other dialect (i.e., Sogn dialect for the Oslo students, and Oslo dialect for the Sogndal students). The gender systems in the two dialects differ: the Sogn dialect makes an obligatory three-gender split (Masculine, Feminine and Neuter) whereas the Oslo dialect only obligatorily makes a two gender distinction. The research question was whether speakers could use gender markers to predict the upcoming target noun in both local and non-local dialect mode, and furthermore, if they correctly could adjust their expectations based on dialect mode. The results showed that the Sogn speakers could predict upcoming linguistic material both in the local and Oslo dialect, but only the stable group were able to adjust their predictions based on the dialect mode. The unstable group applied a more general Oslo-compatible parsing to both the local and the non-local dialect. The Oslo speakers on the other hand were able to use gender markers as predictors only in their own dialect. We argue that the stable Sogn group should be treated as a bilingual group, as they show native-like skills in both varieties, while the unstable Sogn group can be seen as accommodated monolinguals, in that they treat the two varieties as sharing an underspecified grammar. The Oslo group on the other hand lacks sufficient competence in the other dialect to make use of grammatical markers to make predictions.